Social identity and stroke: 'they don't make me feel like, there's something wrong with me'. Issue 4 (2nd November 2012) - Anderson, Sharon; Whitfield, Kyle
Abstract : Over 85% of the people survive stroke; and of those, over 80% are discharged to the community. However, the majority do not recover completely. Loss of identity is a commonly reported experience after stroke. Studies focus on the individual survivors' use of their own cognitive resources to adapt to change, rather than examining the effects of social interactions on stroke survivors' identities. Social relationships are the foundation upon which survivors rebuild skills to engage with the world, yet little is known about the ways in which families, friends and neighbours provide a context for the recreation of a sense of self and activities after stroke. This article draws on situational analysis grounded theory analysis of in‐depth individual interviews with nine middle‐aged survivors of stroke. In situational analysis, the original grounded theory methods proposed by Glaser and Strauss are used; however, the situational context, and how environments and relationships influence actions, is explicitly analysed. Our objective was to understand the ways in which family, social, and community resources might enhance stroke survivors' participation in personally meaningful activities over the long term. The qualitative accounts of these survivors reveal how social support helped them maintain or more importantly regain a position in society. Following any life‐changing event, people's sense of self is fluid. A relevant social position entitles stroke survivors to become actively involved in setting their own goals and maintaining a positive identity. However, as these participants attested, stroke impaired their social position and resources to reject an imposed social position. It was difficult for these survivors to construct a valued social identity without the support of other people. Future studies should explore the consequences of social interactions with others and how social attitudes about stroke disability affects individual's activity options, professional practice, and ultimately development of a positive poststroke identity.